THE ROLE OF GREEN ENERGY IN THE ECONOMY OF UZBEKISTAN - Khaydarova Kamola Akhinjanovna; Mirjalilova Shakhnoza Mirziyod qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In the article, the analysis of the process of formation and popularization of green energy in our country is considered, its current state, prospects and issues necessary for the development of our national economy.